A study on prefabricated bathroom system / Nor Darna Yanto Saaidin - Saaidin, Nor Darna Yanto (Faculty of Architecture, Planning and Surveying, 2008)
Prefabricated bathroom system will provide high technology system which one the latest system in construction industry. This system rarely had been used widely in Klang Valley. The typical system uses a fully furnished where assemble in factory based on the client’s requirement. This means that the system is order-based because most prefabricated export to other countries. This research focused on nature condition of the system in applying to any building. In addition a planning approach including problems and additional cost for installation works for the system. To support this research, two (2) building that was apply prefabricated bathroom system has been taken as case studies at around Klang Valley. In addition, the data were gathered through structured interview and adopted information. From the analysis, it can be found that the cost is expensive for each unit and possible of rare usage among projects. Nevertheless this system is the best benefit in current user. This dissertation gives clear perception to the reader on the quality of prefabricated bathroom system and the information from this analysis can help the reader to choose what the suitable system for using this rare building segments.